Estradiol accelerates liver regeneration through estrogen receptor α - Tsugawa Y; Natori M; Handa H; Imai T (Clinical and Experimental Gastroenterology, 2019)
Yoji Tsugawa,1 Michiya Natori,2 Hiroshi Handa,3 Takeshi Imai11Department of Aging Intervention, National Center for Geriatrics and Gerontology, Obu, Aichi 474-8511, Japan; 2Department of Obstetrics and Gynecology, Tokyo Medical University, Shinjuku, Tokyo 160-8402, Japan; 3Department of Nanoparticle Translational Research, Tokyo Medical University, Shinjuku, Tokyo 160-8402, JapanBackground: We previously demonstrated that liver resection triggers estradiol production, which, in turn, induces the proliferation of hepatocytes to promote liver regeneration in mice. In this study, we demonstrated estradiol-induced estrogen receptor alpha (ERα) expression.Methods: To further explore the role of ERα in estradiol-mediated liver regeneration, in the present study, we confirmed impaired liver regeneration ability in ERα knockout mice.Results: Further analysis during liver regeneration revealed a role for ERα in hepatic steatosis, tumor necrosis factor-alpha and interleukin 6 expression, and nuclear factor-κB and signal transducer and activator of transcription 3 DNA-binding activities.Conclusion: Moreover, estradiol administration accelerated liver regeneration through ERα, indicating the feasibility of the estrogen-ERα axis as a target for accelerating the rate of liver regeneration.Keywords: estrogens, estrogen receptor α; ERα, partial hepatectomy, liver regeneration